A comparison of the behavioral and emotional disorders of primary school-going orphans and non-orphans in Uganda - Musisi, Seggane; Kinyanda, Eugene; Nakasujja, Noeline; Nakigudde, Janet (African health sciences, 2007)
This study investigated the emotional and behavioral problems of orphans in Rakai District, Uganda, and to suggest interventions. Studies, elsewhere, have shown orphans to have high levels of psychological problems. However, in Uganda such studies are limited and no specific interventions have been suggested. Methods: The study employed a cross-sectional unmatched case control design to compare emotional and behavioral problems of 210 randomly selected primary school-going orphans and 210 non-orphans using quantitative and qualitative methods employing standardized questionnaires, Focus Group discussions and selected Key Informant interviews. All children were administered Rutter’s Children’s Teacher Administered Behavior Questionnaire to measure psychological distress and a modified version of Cooper’s Self-Report Measure for Social Adjustment. Standardized psychiatric assessments were done on children scoring > 9 on the Rutter’s Scale, using the WHO-ICD-10 diagnostic checklists. Results: Both orphans and non-orphans had high levels of psychological distress as measured using Rutter’s questionnaire but with no significant statistical difference between the two groups (Rutter score > 9; 45.1% & 36.5% respectively; p= 0.10) and no major psychiatric disorders such as psychotic, major affective or organic mental syndromes. Psychological distress was associated with poor academic performance (p=0.00) in both groups. More orphans, than non-orphans had more common emotional and behavioral problems e.g. more orphans reported finding “life unfair and difficult” (p=0.03); 8.3% orphans compared to 5.1 % of the non-orphans reported having had past suicidal wishes (p=0.30) and more reported past “forced sex / abuse” (p=0.05). Lastly, the orphans’ social functioning in the family rated significantly worse compared to the non-orphans (p= 0.05). Qualitatively, orphans, compared to nonorphans were described as “ needy, sensitive, isolative with low confidence and self-esteem and who often lacked love, protection, identity, security, play, food and shelter.” Most lived in big poor families with few resources, faced stigma and were frequently relocated. Community resources were inadequate. Conclusion: In conclusion, more orphans compared to non-orphans exhibited common emotional and behavioral problems but no major psychiatric disorders. Orphans were more likely to be emotionally needy, insecure, poor, exploited, abused, or neglected. Most lived in poverty with elderly widowed female caretakers. They showed high resilience in coping. To comprehensively address these problems, we recommend setting up a National Policy and Support Services for Orphans and Other Vulnerable Children and their families, a National Child Protection Agency for all Children, Child Guidance Counselors in those schools with many orphans and lastly social skills training for all children.
Keywords: Orphan; Caretaker; Psychological distress; HIV/AIDS